Monocytes in inflammatory bowel disease: phagocytosis and intracellular killing. - Mee, A; Szawatakowski, M; Jewell, D (BMJ Publishing Group, 1980)
The ability of peripheral blood monocytes from patients with ulcerative colitis and Crohn's disease to phagocytose and kill a standard strain of Staphyloccus aureus has been studied. Using lysostaphin, a rapidly acting muralytic enzyme, phagocytosis could be accurately differentiated from intracellular killing. When compared with normal healthy individuals and patients with gastrointestinal diseases not thought to be immunologically mediated, monocytes from patients with inflammatory bowel disease showed a statistically significant increase in the number of bacteria phagocytosed in 2 hours. There was no difference, however, between patients with Crohn's disease and those with ulcerative colitis. For all groups studied, more than 95% of ingested organisms were killed, and there was no difference between groups. These results suggest that peripheral blood monocytes in patients with Crohn's disease and ulcerative colitis are activated. It is unlikely that the granulomata of Crohn's disease result from a defect in the microbicidal function of the monocyte/macrophage system.